Elizabeth Attaway, London preacher and Theologian, 1645–1646. Issue 5 (3rd September 2021) - Kerr, Jason A.
ABSTRACT: This paper reconsiders the 1645–1646 career of Elizabeth Attaway, known primarily to scholars as an early reader of Milton's Doctrine and Discipline of Divorce or as evidence of General Baptist congregations' openness to women's preaching. Evidence of Attaway's career survives primarily in the three parts of Thomas Edwards's 1646 Gangraena, a polemical source that distorts her career even as it provides valuable information. This paper gives an account of the apocalyptic theology that shaped Attaway's decision to "divorce" her husband. It also argues for the independence of Attaway's preaching from established congregations, highlighting her role as the instigator of perhaps the first public preaching by women in civil war London – which happened not in gathered churches, but in public, revival-style exercises. Accordingly, it establishes Attaway as a more significant figure in the religious landscape of 1640s London than previously thought.